Fostering Resilience and Protection: The Role of the Knowledge Hub in Enhancing Critical Infrastructure Security - Levak, Jelena (Crisis Management Days, 2024)
The EU-CIP Knowledge Hub is a new initiative aimed at fostering innovation, collaboration, and advancement within the Critical Infrastructure Protection (CIP) and Critical Infrastructure Resilience (CIR) sectors. This platform is designed to serve as a vibrant ecosystem that enables stakeholders from various fields such as cybersecurity, energy, transportation, and telecommunications to access and share knowledge, results, services, and infrastructures. Key features of the Knowledge Hub include facilitating access to the latest research findings, technological innovations, and policy initiatives. It aims to engage a network of experts and peers dedicated to advancing these fields and contributes to shaping the future direction of related initiatives within the EU. The Hub is positioned as a central meeting point that boosts knowledge sharing and collaborative efforts among all stakeholders, helping them drive innovation, shape policy, and advance the state of critical infrastructure protection and resilience. The Knowledge Hub also emphasizes the socio-economic and environmental impacts of effective critical infrastructure protection, highlighting the benefits of sustainable practices and the integration of cutting-edge technologies like artificial intelligence, blockchain, and IoT. Overall, the EU-CIP Knowledge Hub represents a significant step toward enhancing the resilience and protection capabilities across Europe, fostering a safer and more connected community.